PELATIHAN PENINGKATAN PEMAHAMAN NILAI-NILAI PANCASILA BAGI APARATUR DESA DI KABUPATEN TANGERANG - Nurdin Nurdin (LPPM Institut Pendidikan Nusantara Global, 2025)
The problem of low understanding of Village Apparatus in the Tangerang Regency Government environment has become a concern for the Regional Government. In the era of globalization, global ideology that has become a culture in village communities has become a challenge for Village Apparatus to master the values ​​of Pancasila as a guide in organizing village government. This training aims to improve the competence of Village Apparatus in Tangerang Regency in integrating Pancasila values ​​into the preparation of programs and activities managed by the village government. This training uses a learning presentation approach method related to mastery of concepts, theories and practices to achieve training objectives. The results of this training show that participants have been able to integrate Pancasila values ​​into programs and activities as draft documents for village government development planning in Tangerang Regency.